Developing Avay Audio Daily Conversation as an Instructional Media for Seventh-Grade Junior High School Students: A Research and Development Study - @titis; Sutanti Nita (JOSAR (Journal of Students Academic Research), 2026)
Abstract The objective of this research is to develop "Avay Audio Daily Conversation" as an effective instructional media to improve the speaking skills of seventh-grade junior high school students. This study addresses the common challenges faced by EFL learners, particularly the lack of engaging audio resources and students' hesitation in practicing daily English conversations. The methodology employed in this study is Research and Development (R&D), following the systematic ADDIE model which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. In the analysis phase, it was identified that students required more interactive and accessible audio-based materials to bridge the gap between classroom theory and practical daily usage. The development phase focused on creating high-quality audio recordings and accompanying scripts validated by material and media experts to ensure pedagogical and technical quality. During the implementation phase, the product was tested to measure its practicality and effectiveness in a classroom setting. The findings indicate that the Avay Audio Daily Conversation media is highly valid and significantly aids students in mastering pronunciation and conversational expressions. This study concludes that integrating technology-based audio media into the curriculum provides a solid foundation for communicative competence. The implications suggest that teachers should adopt varied instructional media to foster a more immersive and interactive language learning